From The Theater of Mind to Visual Radio: Transforming Broadcaster Practice in the Age of Media Convergence - Rifqi Aniqo; Bambang Dwi Prasetyo (INJECT (Interdisciplinary Journal of Communication), 2026)
This study examines the transformation of broadcasting practices within the context of media convergence, particularly focusing on the shift from the traditional theater of the mind, which emphasizes auditory imagination, toward visualized radio practices. This transformation not only reconfigures the sensory orientation of radio but also reshapes the performance of broadcasters. Broadcasters are now required to maintain the distinctive characteristic of radio as an imaginative auditory medium while simultaneously adapting to emerging visual and digital media ecosystems. This issue is significant as radio institutions increasingly adopt visual platforms to sustain their relevance in a rapidly evolving, digitally convergent media environment. This study employs a qualitative grounded theory approach, utilizing three stages of coding: open coding, axial coding, and selective coding. The data were collected through in-depth interviews with radio practitioners and supported by observational analysis of visualized radio practices. The findings reveal that broadcasters are no longer limited to on-air performance but are also engaged in live streaming and visual content production. While radio visualization does not fundamentally alter the core production processes of radio, it complements and extends them. This hybrid practice enables radio to remain resilient in the digital era. Furthermore, the study demonstrates that radio visualization has become an essential strategy for broadcasters to sustain their performance, negotiate professional identity, and preserve the theater of the mind within a multimedia environment.